How the church fails businesspeople : and what can be done about it - Knapp, John C. (Grand Rapids, Mich. : W.B. Eerdmans Pub. Co., 2012)
In this book John C. Knapp argues that the church's ambiguous teachings about vocation, money, and business have long contributed to Christians' uncertainty about discipleship in the workplace. Drawing on his own expertise in business ethics and numerous interviews with Christians in diverse occupations, Knapp offers a new theological framework for Christian life in the world of business. --from publisher description
Part I. Worlds apart -- ch. 1. The world of business -- ch. 2. The world of church -- ch. 3. Uneasy bedfellows : money and the church -- ch. 5. Divided worlds, divided lives -- Part II. Toward coherence -- ch. 6. Rethinking Christian vocation -- ch. 7. A moral theology for work -- ch. 8. A workplace awakening -- ch. 9. The church's potential.
Includes bibliographical references (p. 157-158) and indexes.
Keywords: Work -- Religious aspects -- Christianity; Employees -- Religious life -- United States